Cocrystal pleomorphism-inspired drug nanoassembly for pulmonary-endothelium targeting and pulmonary hypertension treatment - Makhloufi Zoulikha; Jiahui Zou; Pei Yang; Jun Wu; Wei Wu; Kun Hao; Wei He (Acta Pharmaceutica Sinica B)
Endothelial dysfunction is one of the early triggers of vascular remodeling during pulmonary hypertension (PH) with complex predisposing mechanisms, mainly via an unbalanced generation of vasoactive factors, increased expression of growth factors, prothrombotic elements, and inflammatory markers. Conventional treatment regimens are restricted to a single therapeutic pathway, which usually leads to limited clinical outcomes. Combination therapies targeting multiple cells and several signaling pathways are increasingly adopted in PH treatment. Herein, inspired by the cocrystal pleomorphism theory, we prepared rod-shaped nanococrystals of the endothelin-1 (ET-1) receptor antagonist (bosentan, BST) and the anti-inflammatory drug (andrographolide, AG) for targeting the pulmonary endothelium and alleviating PH. The 525 nm-sized co-delivery system displayed a rod-like morphology, preferentially accumulated in the pulmonary endothelium and alleviated pulmonary artery (PA) remodeling. A three-week treatment with the preparation significantly alleviated the monocrotaline (MCT)- or Sugen 5416/hypoxia (SuHx)-induced PH by reducing the pulmonary artery pressure, increasing the survival rate, improving the hemodynamics, and inhibiting vascular remodeling. Mechanistically, the nanococrystals collaboratively repaired endothelial dysfunction by suppressing the pathways of ET-1/NF-κB/ICAM-1/TNF-α/IL-6. In conclusion, the cocrystal-based strategy offers a promising approach for constructing co-delivery systems. The developed rod-shaped nanococrystals effectively target the pulmonary endothelium and relieve experimental PH.